New Archaeozoological Studies of Medieval Bilyar - Shaymuratova Dilyara N.; Askeyev Igor V.; Shakirov Zufar G. (Археология евразийских степей, 2021)
The paper discusses a new study of fi sh and bird remains from excavation XLIV of Bilyar fortifi ed settlement, founded in order to study a large brick building located in the so-called “Inner City” – the part of the settlement with the highest status. The aim of the study was a comprehensive analysis of faunal remains extracted from the cultural layer using the method of layer-by-layer sampling and sieving. On the basis of bone remains and scales, a total 23 fi sh species were identifi ed with predominant remains of large species: Starred sturgeon, Zander, Sterlet and Whitefi sh. The predominance of large species indicates that fi shery was practiced on the Volga and Kama rivers, and the bulk of the fi sh consumed at the site was imported. The species composition of birds is high and diverse – 40 species of wild and 3 species of domestic birds with predominant domestic chicken. Of interest among wild birds are the finds of skeleton fragments of the birds of prey of the Accipitriformes and Falconiformes order, which indicates the presence of falconry in the area, and its high social status.